2022
DOI: 10.1111/jvim.16525
|View full text |Cite
|
Sign up to set email alerts
|

Domestic cat hepadnavirus associated with hepatopathy in cats: A retrospective study

Abstract: Background Whether domestic cat hepadnavirus (DCH) infection is associated with clinical disease remains to be determined. Objectives To determine the relationship between DCH detection, hematology, serum bichemistry and liver histology in DCH‐positive cats. Animals One thousand twenty‐two cats in Thailand without concurrent diseases and not undergoing treatments adversely affecting the liver. Methods Retrospective cross‐sectional study. Samples derived from cats with concurrent virus detection were excluded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…This study showed that DCH is circulating among cats in Hong Kong, with a molecular prevalence of 11.1%, as measured by DCH DNA detection in whole blood. The prevalence in other regions varies widely, with DCH-positive cats apparently uncommon in the USA (0.2%) [ 11 ], Japan (0.78%) [ 12 ], and UK (1.9%) [ 10 ]; whereas virus DNA has been readily detected in cats in Australia (6.5%) [ 6 ], Italy (10.8%; 4.2%) [ 7 , 26 ], Thailand (18.5%) [ 15 ], and Malaysia (12.3%) [ 9 ]. Despite study design differences, it is likely that there are genuine regional differences in DCH prevalence, potentially caused by various transmission dynamics, as with human HBV [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study showed that DCH is circulating among cats in Hong Kong, with a molecular prevalence of 11.1%, as measured by DCH DNA detection in whole blood. The prevalence in other regions varies widely, with DCH-positive cats apparently uncommon in the USA (0.2%) [ 11 ], Japan (0.78%) [ 12 ], and UK (1.9%) [ 10 ]; whereas virus DNA has been readily detected in cats in Australia (6.5%) [ 6 ], Italy (10.8%; 4.2%) [ 7 , 26 ], Thailand (18.5%) [ 15 ], and Malaysia (12.3%) [ 9 ]. Despite study design differences, it is likely that there are genuine regional differences in DCH prevalence, potentially caused by various transmission dynamics, as with human HBV [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…No correlation was observed between serum ALT levels, a marker of hepatocellular injury, and DCH DNA detection, or virus load. In contrast, serum ALT was significantly associated with DCH DNA positivity in studies from Thailand and Malaysia [ 9 , 15 ]. A reported association between age >2 years and DCH detection [ 13 ] provided the rationale to exclude hyperthyroidism—a common cause of ALT elevation in cats > 8 years [ 16 ]—as a confounder in ALT analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following its initial discovery in Australia, investigation of DCH prevalence of this virus in cats from different countries have been carried out, with positive cases reported in Italy, Thailand, Malaysia, the United Kingdom, Japan, the United States, Hong Kong, and Türkiye [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, there is a lack of information regarding this virus in Taiwan, highlighting the importance of DCH investigation.…”
mentioning
confidence: 99%